Long-term wash-resistant effects of brief interaction of xanomeline at the M1 muscarinic receptor - De Lorme, Kayla C. (2006)
Compared to other M(1)muscarinic acetylcholine receptor (M(1) mAChR) agonists, xanomeline demonstrates both reversible and persistent modes of binding to the receptor. In our study, we investigated the long-term consequences of brief incubation of Chinese hamster ovary cells expressing M(1) mAChR (M(1)-CHO) with low concentrations of xanomeline followed by washing off the free drug. Thus, M(1)-CHO cells were exposed to 100 nM xanomeline for 1 h then washed extensively. Washed cells were either used immediately for binding assays or incubated for 23 h in the absence of free xanomeline. Only the latter treatment conditions resulted in marked attenuation of binding of the muscarinic radioligand [(3)H]N-methylscopolamine ([(3)H]NMS) to intact cells. Shortening the xanomeline pretreatment period to 1 min had the same trends as the 1 h pretreatment, implying that xanomeline binds instantly to the receptor to elicit long-term wash-resistant effects. Presence of atropine during the brief period of xanomeline pretreatment did not markedly modulate xanomeline’s long-term effects, which suggests that persistent anchoring of the xanomeline molecule to the M1 receptor takes place at a site distinct from the orthosteric binding domain. Our findings suggest the possibility of a time-dependent transition of the conformation of the muscarinic M(1) receptor-xanomeline complex between states that vary in their ability to bind [(3)H]NMS. However, possible involvement of other mechanisms of long-term receptor regulation cannot be discounted.